Endocarditis infecciosa (2015)
ABSTRACT: Infective endocarditis is a disease caused by colonization and proliferation of infectious agents on the endothelial surface of the heart. Its clinical presentation is variable, depending upon conditions of the patient, such as immunosuppression, presence of prosthetic material, intravenous drug use, and the etiologic agent. Diagnosis is usually established through the addition of elements such as medical history, physical examination, results of blood cultures, echocardiography and other aids. We present the case of an adult male who came to the hospital with fever and symptoms and signs of acute heart failure. The presence of a systolic murmur was documented in the aortic area, and the echocardiogram revealed severe valve regurgitation and a vegetating lesion on the bicuspid aortic valve. He required valve replacement and completed antibiotic treatment based on the sensitivity of the Streptococcus mitis strain that was demonstrated in the blood cultures.